A grounded theory study of 'turning into a strong nurse': Earthquake experiences and perspectives on disaster nursing education. (September 2015) - Li, Yan; Turale, Sue; Stone, Teresa E.; Petrini, Marcia
Summary: Background: While Asia has the dubious distinction of being the world's most natural disaster-prone area, disaster nursing education and training are sparse in many Asian countries, especially China where this study took place. Objective: To explore the earthquake disaster experiences of Chinese nurses and develop a substantive theory of earthquake disaster nursing that will help inform future development of disaster nursing education. Design: A qualitative study employing grounded theory, informed by symbolic interactionism. Participants and Setting: Fifteen Chinese registered nurses from five hospitals in Jiangxi Province who undertook relief efforts after the 2008 Wenchuan Earthquake. Methods: Data were collected in 2012–2013 in digitally-recorded, semi-structured, in-depth interviews and reflective field notes, and analyzed using Glaser's grounded theory method. Results: Participants were unprepared educationally and psychologically for their disaster work. Supporting the emergent theory of "working in that terrible environment", was the core category of "turning into a strong nurse", a process of three stages: "going to the disaster"; "immersing in the disaster"; and "trying to let disaster experiences fade away". The participants found themselves thrust in "terrible" scenes of destruction, experienced personal dangers and ethical dilemmas, and tried the best they could to help survivors, communities and themselves, with limited resources and confronting professional work. Conclusions: Our rich findings confirm those of other studies in China and elsewhere, that attention must be paid to disaster education and training for nurses, as well as the mental health of nurses who work in disaster areas. Emergent theory helps to inform nurse educators, researchers, leaders and policy makers in China, and elsewhere in developing strategies to better prepare nurses for future disasters, and assist communities to prepare for and recover after earthquake disasters. Highlights: Coping with disaster work required three phases of turning into a 'strong nurse'. No participants had received disaster nursing training before being sent to the earthquake disaster zone, significantly impacting on their ability to cope, to understand expectations and help victims in the 'terrible environment' All spoke of the ongoing effects of the disaster on their mental health and their lack of preparedness to help traumatized victims. All participants believed that disaster nurse training should be readily available in the future and suggested key areas to include in courses.